Perspektif Yuridis dan Hukum Islam terhadap Keabsahan Ayah Angkat sebagai Wali Nikah - Selinah, Selinah; Akbarizan, Akbarizan (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
Marriage registration is often a challenge for marriage registrars at the sub-district level because people often do not understand the laws and regulations related to marriage. One of the obstacles that often arises is the inconsistency of data regarding the status of guardians, even though administratively all requirements have been met during registration. This problem generally occurs when the bride-to-be is an adopted child, where the identity on the birth certificate and ID card includes the surname of the adoptive father. This situation causes difficulties in the recording process, especially related to the determination of the legal guardian as one of the pillars of marriage. If the adoptive father's name is included in the marriage book, this can cause problems later on, such as in terms of inheritance rights and other legal aspects. This research is a library research using a normative approach. There are several problem formulations in this study, including First, how is the perspective of Islamic law on the validity of the adoptive father as a guardian in marriage. Second, what is the juridical perspective regarding the adoptive father as the guardian of the marriage. The method of collecting legal materials used is the collection of library materials, because this method is in accordance with the type of research that has been described earlier. The results of the study show that in the view of Islamic law, nasab describes a strong kinship bond, especially in the relationship of descent between children and parents. The person who has the main right to be the guardian for a woman who is going to marry is the guardian of the nasab line. This is because the nasab relationship is considered the strongest and closest bond, thus providing special rights in terms of guardianship. Meanwhile, Article 6 paragraph (6) of the Law on Marriage and Article 20 paragraph (2) in the Compilation of Islamic Law regarding the position of the marriage guardian show that the adoptive father cannot be the marriage guardian for the Muslim bride. This is because the adoptive father is not included in the category of guardian nasab, because there is no blood relationship with the bride. Therefore, for the adopted children of Muslim women, the right as a guardian falls to the guardian of the judge.